Water and Sanitation Committees For Sustainable Service Delivery in Ghana: The Case of Nanumba North District, Northern Region, Ghana (Journal of Science and Technology, 2016)
The achievement of the targets in terms of water and sanitation coverage in Ghana depends to a large extent on the establishment of institutions like Water and Sanitation Committees (WATSAN) for effective operation and maintenance of the water and sanitation facilities. This paper is based on the assessment of WATSAN in the Nanumba North District in the Northern Region of Ghana, where considerable investment in the sector has been made. The study established, among others, that the operations of the WATSAN were limited in terms of scope and effectiveness mainly due to their limited financial strength. It revealed that the institutional environment within which WATSAN operate as well as their modus operandi determined the communities' response to the maintenance and service delivery challenges. In view of these it is recommended that the institutional framework and composition of WATSAN be strengthened and scaled upwards to the District Assembly and the members should be financially rewarded from the proceeds of user fees so that they can effectively ensure sustainable water and sanitation services delivery. These measures are in line with the principles of the new public management strategies for public service delivery.